2012
DOI: 10.1152/ajpregu.00053.2011
|View full text |Cite
|
Sign up to set email alerts
|

Increased thermogenic capacity of brown adipose tissue under low temperature and its contribution to arousal from hibernation in Syrian hamsters

Abstract: Kitao N, Hashimoto M. Increased thermogenic capacity of brown adipose tissue under low temperature and its contribution to arousal from hibernation in Syrian hamsters. Am J Physiol Regul Integr Comp Physiol 302: R118 -R125, 2012. First published October 12, 2011 doi:10.1152/ajpregu.00053.2011.-Brown adipose tissue (BAT) is thought to play a significant physiological role during arousal when body temperature rises from the extremely low body temperature that occurs during hibernation. The dominant pathway of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 44 publications
2
21
0
Order By: Relevance
“…Animals hibernating at temperatures below their hypothalamic set-point may be particularly dependent on heat generated by brown adipose tissue. While electromyographic activity from shivering has been observed at T b 's as low as 47C (Tøien et al 2001), shivering is not thought to be an effective heat generator at this temperature (Kitao and Hashimoto 2012). Brown adipose tissue, on the other hand, upregulates UCP-1 upon cold exposure, and the highest levels are found in hibernators that are actively generating heat (Barger et al 2006), indicating functionality at very low temperatures.…”
Section: Discussionmentioning
confidence: 98%
“…Animals hibernating at temperatures below their hypothalamic set-point may be particularly dependent on heat generated by brown adipose tissue. While electromyographic activity from shivering has been observed at T b 's as low as 47C (Tøien et al 2001), shivering is not thought to be an effective heat generator at this temperature (Kitao and Hashimoto 2012). Brown adipose tissue, on the other hand, upregulates UCP-1 upon cold exposure, and the highest levels are found in hibernators that are actively generating heat (Barger et al 2006), indicating functionality at very low temperatures.…”
Section: Discussionmentioning
confidence: 98%
“…Forskolin activates the adenylyl cyclase enzyme directly and increases the intracellular levels of cAMP with a Kd=14.8×10 −9 M [8]. Forskolin is known as an inducer of thermogenic response in BAT [9]. …”
Section: Introductionmentioning
confidence: 99%
“…Likewise, social separation alone suppressed muscularity and adiposity with female biases. Consistent with greater bioenergetic depletion [86, 87], social separation reduced the sizes of brown adipose depots in males, but not in females. Social separation decreased adrenal weights in females only, and we have reported that this effect was more robust in females than in males [36].…”
Section: Discussionmentioning
confidence: 98%